Environmental, Social and Governance (ESG) Evaluation and Organizational Attractiveness to Prospective Employees: Evidence From Japan - Liu, Lian; Nemoto, Naoko (Journal of Accounting and Finance, 2021)
This study hypothesized that firms’ Environmental, Social and Governance (ESG) evaluation is related positively to their attractiveness to prospective employees. Although growing number of researches have been focusing on relations between ESG evaluation and corporate financial performance, few researches have investigated the link between ESG evaluation and corporate attractiveness as employers. Results indicate ESG evaluation is related to firms’ attractiveness as employers, suggesting that a firm’s high ESG scores may provide a competitive advantage in attracting human talents and enhancing corporate value. At a time when corporate success depends on a high-level staff, the need for corporate to improve ESG evaluation is intensifying. Regarding the impact of ESG component, the study shows Environmental factor has significant positive impact on attractiveness of larger firms, while Governance is most relevant for smaller firms.